PERAN PENDIDIKAN LINGKUNGAN HIDUP DALAM MENGURANGI TINDAKAN PENCEMARAN LINGKUNGAN OLEH MASYARAKAT DESA GAMEL - Lestari, Dian Mawar; Saajidah, Nasywaa; Camila, Laitsza Afza (CV. Kalimasada Group, 2024)
This article examines the important role of environmental education in reducing environmental pollution by society. This research aims to evaluate the effectiveness of environmental education in changing the behavior of the Gamel Village community towards waste management and pollution. The methodology used was interviews with various members of the Gamel Village community to obtain their views on environmental outreach and education. Interview results show that frequent outreach about the negative impacts of waste and how to handle household waste is considered important by several respondents, although there are still many people who do not fully understand the negative impacts of waste and therefore still throw rubbish carelessly. One proposed approach is the use of organic materials to create more environmentally friendly waste. Several respondents noted that people who receive environmental education and information show higher levels of awareness about plastic pollution and tend to reduce their dependence on single-use plastics. Overall, this research shows that environmental education can increase pro-environmental awareness and behavior in the Gamel Village community. Intensive and continuous education, together with supportive regulations, can contribute significantly to reducing environmental pollution.